LIFEPLAN: A worldwide biodiversity sampling design. - Bess Hardwick; Deirdre Kerdraon; Hanna M K Rogers; Dimby Raharinjanahary; Eric Tsiriniaina Rajoelison; Tommi Mononen; Petteri Lehikoinen; Gaia Banelyte; Arielle Farrell; Brian L Fisher; Tomas Roslin; Otso Ovaskainen (PLoS ONE)
As the technology for mass identification of species is advancing rapidly, we developed a field sampling method that takes advantage of the emerging possibilities of combining sensor-based data with automated high-throughput data processing. This article describes the five field sampling methods used by the LIFEPLAN project to collect biodiversity data in a systematic manner, all over the world. These methods are designed for use by anyone with basic biology or ecology knowledge from the higher education or university level. We present the selection and characteristics of international sampling locations for urban and natural sites, as well as the nested scale design in the Nordic countries and Madagascar. We describe the steps to collect sequences of animal images (.jpg) from infrared triggered camera traps, audio data (.WAV) of environment sounds from audio recorders, invertebrate samples in ethanol from Malaise traps for DNA metabarcoding, as well as both soil samples and 24-hour air samples obtained from cyclone samplers for fungal DNA metabarcoding. To ensure the usability and consistency of the data for future use, we pay particular attention to the metadata collected. In specifying the current sampling protocols, we note that technology will continue to improve and evolve. Hardware will also change within a short time period, with the advantage of improving the equipment used for collecting samples. Thus, we present examples of the samples collected by each current sampling method, to be used as a baseline or in comparison with different equipment models.